Enhanced nonlinear absorption and ultrafast carrier dynamics in graphene/gold nanoparticles nanocomposites. (July 2019) - Yu, Yang; Si, Jinhai; Yan, Lihe; Li, Ming; Hou, Xun
Abstract: The nonlinear optical response of gold nanoparticles/reduced graphene oxide (AuNPs/rGO) nanocomposites prepared by laser ablation method was studied using a femtosecond laser open-aperture (OA) Z-scan method, and an enhanced nonlinear absorption effect was observed. Using the femtosecond time-resolved pump-probe measurements, the nonlinear response mechanism in the hybrid was studied. When graphene was excited by an ultrashort laser pulse, the bleaching of valence band (VB) and the filling of conduction band (CB) took place, causing a saturable absorption (SA) effect. When decorated with gold nanoparticles, the excited carriers from the CB of graphene could transfer to the sp band of the metal before returning to the VB of graphene. This process would take place in a much longer time scale (∼50 ps) than the direct relaxation in pure graphene, causing the enhancement of the SA effect. The excited carrier dynamics were further demonstrated using femtosecond time-resolved transient absorption spectroscopy, and the interband relaxation of the excited electrons from the sp band of AuNPs to the CB of graphene was observed, resulting in the further filling of the CB of graphene and enhancement of the SA effect.